A Successive Selection Method for finite element model updating. (March 2016) - Gou, Baiyong; Zhang, Weijie; Lu, Qiuhai; Wang, Bo
Abstract: Finite Element (FE) model can be updated effectively and efficiently by using the Response Surface Method (RSM). However, it often involves performance trade-offs such as high computational cost for better accuracy or loss of efficiency for lots of design parameter updates. This paper proposes a Successive Selection Method (SSM), which is based on the linear Response Surface (RS) function and orthogonal design. SSM rewrites the linear RS function into a number of linear equations to adjust the Design of Experiment (DOE) after every FE calculation. SSM aims to interpret the implicit information provided by the FE analysis, to locate the Design of Experiment (DOE) points more quickly and accurately, and thereby to alleviate the computational burden. This paper introduces the SSM and its application, describes the solution steps of point selection for DOE in detail, and analyzes SSM׳s high efficiency and accuracy in the FE model updating. A numerical example of a simply supported beam and a practical example of a vehicle brake disc show that the SSM can provide higher speed and precision in FE model updating for engineering problems than traditional RSM. Highlights: A new method based on response surface method is proposed. Experimental design points are selected adaptively to approach the optimal updating value. The method improves the efficiency and accuracy in model updating, when compared to the traditional RSM. The proposed method is illustrated by a numerical example of a simply supported beam.